Maldives : Technical Assistance Report-Modernizing the Goods and Services Tax. (IMF Staff Country Reports; Country Report ;, 2022)
This report reviews the Goods and Services Tax (GST) regime in the Maldives and identifies policy and legal reform options to support its modernization, as well as enhancing efficiency, equity, and revenue mobilization. Despite five existing amendments to the Goods and Services Tax Act (GSTA) and 28 amendments to the associated regulations, the core parameters of the GST have barely changed in nearly 12 years. In addition, rapid changes to global business models and the increasing digitalization of the Maldivian economy have made key features of the legislation - such as place of supply rules - increasingly inadequate. The mission identified several key GST policy reforms and proposed legal redrafting recommendations that should be prioritized by the authorities in the upcoming reform window. Table 1 summarizes the potential revenue implications and implementation timeline of the main policy measures proposed.